A camera trap assessment of terrestrial vertebrates in Bwindi Impenetrable National Park, Uganda - Mugerwa, B; Sheil, D.; Ssekiranda, P; Heist, M.V.; Ezuma, P. (Wiley, 2013)
We placed camera traps for a month at sixty locations in Bwindi Impenetrable National Park to determine the species composition and distribution of medium‐to‐large terrestrial vertebrates. A total of 15912 images were recorded from 1800 camera trap days. These provided a total of 625 and 338 camera events when filtered by hour and day, respectively. Twenty mammal species were recorded from 594 and 314 camera events by hour and day, respectively. Four bird species were recorded from 31 and 24 camera events by hour and day, respectively. The African golden cat Profelis aurata Temminck was recorded from 27 and nineteen camera events by hour and day, respectively. The black‐fronted duiker Cephalophus nigrifrons Gray was most frequently photographed with 179 and 65 camera events by hour and day, respectively. Analyses reveal two species possessed a significantly interior‐biased distribution. One species showed an edge‐biased pattern. Five species were detected to have significantly biased altitudinal distributions with higher elevations. Distance to park edge and elevation can significantly influence species distribution. The selective use of the park limits the area that each species utilizes, with implications for maximum population sizes and viability. Our observations provide a baseline for long‐term terrestrial vertebrate monitoring in Bwindi.